Compostos de metais de transição neuroativos: investigações fotoquímicas, fotofísicas, físico-químicas e citotoxicidade para drogas neuroativas em fase III - Camilo, Mariana Romano (Universidade Federal de São Carlos, 2010)
The photochemical and photophysical properties of the cis-[Ru(α-diimine)2(4Apy)2]2+ complexes where 4Apy= 4-aminopyridine, α-diimine = 1,10 -phenanthroline (phen) (1), 4,7 -diphenyl-1,10 -phenanthroline (Ph2phen) (2), 2,2 -bipyridine (bpy) (3) and 4,4 -dimethyl-2,2 -bipyridine (Me2bpy) (4) are reported. The four complexes have been characterized using HPLC, 1H NMR, UV-vis and emission spectroscopy. The Xray structure of complexes 1 and 3 were also obtained. The complexes are thermally stable throughout the course of many hours in non-aqueous and aqueous solution and highly colored. The absorptions are characterized by two broad shoulders for the phen derivatives complexes and one peak and one shoulder for the bpy derivatives. The four complexes show two emissive states at room temperature in fluid solution; their emission lifetimes (Tem) are solvent (CH3CN and DMF), excitation wavelength and α-diimine ligand dependents and are assigned to the population of two different MLCT (3MLCT and 1MLCT) excited states. Upon photolysis in acetonitrile solution, accompanied by spectroscopic techniques (UV-vis, luminescence, 1H NMR, HPLC), these cis-[Ru(α-diimine)2(4Apy)2]2+ complexes undergo 4Apy dissociation to give the mono-acetonitrile complex (for 2, 3 and 4) and the bis-acetonitrile complex (for 1).The substitution quantum yield (Osubs) (Yirr = 420 nm) was high for 1 (0.233) but decreased for complexes 2 (0.044), 3 (0.145) and 4 (0.152); the range of kobs (rate constant for the substitution reaction) values is seven times higher in magnitude from the slowest photochemical reaction 2 to the fastest one 1. Our spectroscopic data show and DFT/TD-DFT calculations confirm that both α-diimine ligand and 4Apy ligands act as a good electron donor ligand. Among the α- diimine ligand studied the phenanthroline is the electron-richest ligand, which behaves as a good α-donor toward the Ru(II) atom in complex 1 compared to Ph2phen, bpy and Me2bpy in complexes 2, 3 and 4 respectively. On the basis of this data is reasonable to assume that the Ru-4Apy bond would make weaker the XVIII ruthenium atom becomes more electron rich favoring its labilization. Indeed, the NBO (Natural Bond Orbital) charge analysis indicate a strong variation of the charge on the ruthenium ion, that is, +0.287 (1), and ~+0.63 in complexes 2, 3 and 4. The negative charge on the phen ligand is also significantly reduced to ~0.12 (1) and slightly reduced ~0.05 in complexes 2, 3 and 4 suggesting a stronger α-donation and weaker back-donation in complex 1 compared to complexes 2, 3 and 4. As a consequence the ligand field of the complex is decreased, which decreases the energy differences between the t2g and eg* of Ru(II). Doing so, the MLCT and MC states will approach increasing the photoreactivity of the complex. The feasibility of 4Apy release in 1 can be explained by the near proximity of the two low lying energy MLCT/MC states at 3.74 eV (demonstrated by TD-DFT calculations) which can be easily populated by light irradiation. This is probably the key of the photodissociation mechanism of 4Apy in this molecule and its derivatives.
Neuroactive transition metal compounds: photoquemistry, photophysics, physico-chemistry investigations and cytotoxicity for neuroactive drugs in phase III
Keywords: Química inorgânica; Complexos de rutênio; Aminopiridina; Fotoquímica; TD-DFT (Métodos de cálculos computacionais); CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA